Exploring the new normal practices in Thai University EFL classrooms : voices of the teachers and students - Marlon D. Sipe,; Pragasit Sitthitikul, (Penerbit Universiti Kebangsaan Malaysia, 2022)
This investigation, through a mixed-methods approach, explored the practices of university teachers and students under the new normal. Framed within Anderson’s (2004) Theory of Online Learning, this study was aimed at answering two research questions: (a) What do the teachers and students see as challenges in terms of teaching and learning English in the university classrooms? (b) What are the proposed ways of effective teaching and learning in the new normal classroom situation? About 342 students and 25 teachers participated in the survey and a number of them, purposively chosen, took part in the interview. The Yamane formula was adopted to determine the sample size and that the participants for the survey were randomly selected. The findings revealed that teaching and learning had challenges in common – issues on participation, risks of cheating, internet, and disruption. The study also proposes a few ways on how to teach and learn English as a Foreign Language (EFL) effectively in the new normal. These include: having fast and stable internet, enabling of cameras, using laptop computers over smaller devices, having an online group for the class, among other suggestions. These challenges and proposed ways, however, can also be observed and applied in other non-EFL courses.